The impact of etiology and duration of deafness on speech perception outcomes in SSD patients - Kurz, Anja; Grubenbecher, Marius; Rak, Kristen; Hagen, Rudolf; Kühn, Heike (European archives of oto-rhino-laryngology, 2019)
Objective To investigate a cohort of adult single-sided deafness (SSD) patients who received a cochlear implant and to determine the impact of underlying causes of etiology and duration of deafness on outcome Study design Retrospective data analysis Setting Tertiary referral centre with a large cochlear implant program Subjects and methods A demographic description of 55 adult patients implanted between 2009 and 2016. The best available speech perception score in every patient using the Freiburg Numbers, Freiburg Monosyllables and the Hochmair-Schulz-Moser (HSM) sentence test measured at the 1-, 3-, 6- and 12-month intervals, and the yearly follow-up appointments were examined. A multivariate regression analysis was conducted on the variables speech test, duration of deafness and etiology. Patients were split into four groups according to their duration of deafness (shorter duration of 10 years or less versus longer duration of more than 10 years) and etiology (inflammatory disease versus other causes). Results The median word reception score for the Monosyllables at 65 dB SPL were 43.75% (IQR: 29.38) and 67.50% (IQR: 25.63) at 80 dB SPL at 1 year following cochlear implantation. The median percentage score correct for the HSM sentence test was 80% (IQR: 62.95). Etiology of the reviewed patient cohort revealed that most frequent causes for deafness were sudden hearing losses and inflammatory etiologies, e.g. otitis media, labyrinthitis, meningitis, cholesteatoma or mumps. The duration of deafness was not significantly associated with poor speech perception outcome. A significant correlation was found for inflammatory diseases and duration of deafness of longer than 10 years. Conclusion The etiology and duration of deafness are important factors for the estimated outcome in speech perception in SSD patients. Presented data reveal that an inflammatory disease leading to deafness in combination with a long duration of deafness (10 + years) lead to poorer speech perception outcomes.